Exploring destination personality and electronic word of mouth influences on travel decisions using structural equation modelling / An Nur Nabila Ismail, Nik Mohamad Shamim Nik Mohamad Zainordin and Yuhanis Abdul Aziz - Ismail, An Nur Nabila; Nik Mohamad Zainordin, Nik Mohamad Shamim; Abdul Aziz, Yuhanis (Universiti Teknologi MARA, Kelantan, 2022)
Langkawi Island is one of the top tourist destinations in Malaysia. Yet, there are still several factors that can contribute to its competitiveness in the tourism industry. The study emphasises destination personality as the factor that can stimulate travellers in determining holiday destinations. As information is considered important to tourists in selecting a holiday destination, the study also investigates the marketing effort by observing the elements of electronic word of mouth as sources for travellers to have some knowledge about the destination before they select it. 503 respondents were involved in this study and data were analysed using Structural Equation Modelling in Smart-PLS. The finding indicates that destination personality and electronic word of mouth have a significant relationship with destination choice. This finding helps the policymaker and business providers strategies their marketing effort to make Langkawi a competitive destination.